Possible Implication of Local Immune Response in Darier's Disease: An Immunohistochemical Characterization of Lesional Inflammatory Infiltrate - Clelia Miracco; Francesco Pietronudo; Vasileios Mourmouras; Michele Pellegrino; Monica Onorati; Maria Grazia Mastrogiulio; Luca Cantarini; Pietro Luzi (Mediators of Inflammation)
Cell-mediated immunity is considered to be normal in Darier's Disease (DD), an inherited skin disorder complicated by skin infections. To date, there are no investigations on the local inflammatory infiltrate in DD skin lesions. In this immunohistochemical study we characterized and quantified it, making comparisons with two other inflammatory skin disorders, that is, pemphigus vulgaris (PV) and lichen ruber planus (LRP), and with the normal skin (NSk). We found a significant (𝑃<.05) decrease of CD1a+ Langerhans cells (LCs) in DD, compared to PV, LRP, and NSk, and of CD123+ plasmacytoid dendritic cells (pDCs), compared to PV and LRP. We hypothesize that the genetic damage of keratinocytes might result in a loss of some subsets of dendritic cells and, consequently, in an impaired local immune response, which might worsen the infections that inevitably occur in this disease.